Microwave-assisted Fenton's oxidation of amoxicillin
Advanced oxidation processes (AOPs) have been increasingly applied to emergent pollutants degradation. Although, homogeneous reaction by classical Fenton enables amoxicillin degradation, high iron catalyst concentrations are needed, raising environmental concerns. This work proposed an innovative and cheap solution to degrade amoxicillin by combining microwave with Fenton's reaction. The main operational parameters were optimized step-by-step (hydrogen peroxide and ferrous ion concentration and microwave power). Amoxicillin oxidation was significantly improved over classical Fenton's reaction. In fact, in less than 5 min (P = 162 W, [H2O2](0) = 2.35 mg L-1, [Fe2+](0) = 95 mu g L-1) amoxicillin was no longer detected in the reaction system. A semi-empirical kinetic model was proposed to predict the two-stage decay curves at any conditions within the studied parameters and the adequacy of the model was statistically evaluated.